2022
DOI: 10.3389/fphys.2022.999263
|View full text |Cite
|
Sign up to set email alerts
|

Contrastive learning and subtyping of post-COVID-19 lung computed tomography images

Abstract: Patients who recovered from the novel coronavirus disease 2019 (COVID-19) may experience a range of long-term symptoms. Since the lung is the most common site of the infection, pulmonary sequelae may present persistently in COVID-19 survivors. To better understand the symptoms associated with impaired lung function in patients with post-COVID-19, we aimed to build a deep learning model which conducts two tasks: to differentiate post-COVID-19 from healthy subjects and to identify post-COVID-19 subtypes, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, this is in contrast with the findings of R inaldo et al [ 13 ] and B eaudry et al [ 5 ], who did not find any association between dyspnoea and cardiopulmonary impairment or lung function parameters in COVID-19 patients 3–6 months post-infection. Indeed, L i et al [ 19 ] demonstrated the presence of two different latent phenotypes using a volume-independent contrastive learning model with inspiratory and expiratory chest computed tomography (CT) images in 140 post-COVID-19 patients, one with normal volumes and D LCO but CT signs of air trapping and one with reduced volumes and D LCO but only an interstitial fibrotic like pattern.…”
mentioning
confidence: 99%
“…However, this is in contrast with the findings of R inaldo et al [ 13 ] and B eaudry et al [ 5 ], who did not find any association between dyspnoea and cardiopulmonary impairment or lung function parameters in COVID-19 patients 3–6 months post-infection. Indeed, L i et al [ 19 ] demonstrated the presence of two different latent phenotypes using a volume-independent contrastive learning model with inspiratory and expiratory chest computed tomography (CT) images in 140 post-COVID-19 patients, one with normal volumes and D LCO but CT signs of air trapping and one with reduced volumes and D LCO but only an interstitial fibrotic like pattern.…”
mentioning
confidence: 99%
“…Regardless of calculated percentages, modern methods of radiological analysis such as a contrastive learning model used by Li et al [51] manage to distinguish clusters of post-COVID-19 patients-in the mentioned study, it was an air-trapping pattern (due to some small airways disease involvement) and an interstitial fibrotic-like pattern, while the latter were hospitalized more often (90 vs. 67%) and had lower FVC%, TL,CO%, TLC, and higher RV/TLC as well as more ground glass opacities during assessment after the median time of 113 days from COVID 19. These data look promising regarding its comparability to our clinical phenotype distinction; the pulmonary phenotype group presented with alterations in T L,CO %, RV%, TLC% and absolute values of FVC and FEV1.…”
Section: Discussionmentioning
confidence: 99%
“…The cluster-specific characteristics, as detailed in ( Li et al, 2022 ), are outlined below (see also Table S1 ) to aid in establishing correlations with CFPD-based variables. C1 had a female-dominant composition (68.37 % females), while C0 and C2 had a more balanced distribution of males and females.…”
Section: Methodsmentioning
confidence: 99%
“…These biomarkers serve to monitor disease progression, define disease subtypes, predict health trajectories, and inform product and clinical trial designs ( Couper et al, 2014 ). For instance, a recent study, using deep learning in post-COVID-19 CT lung images, identified two distinct clusters ( Li et al, 2022 ). Cluster 1 (C1) was characterized by a female-dominant group with small airway disease, while Cluster 2 (C2) consisted of older individuals with fibrotic-like lung characteristics.…”
Section: Introductionmentioning
confidence: 99%